The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/deci.12140
|View full text |Cite
|
Sign up to set email alerts
|

Designing Multi‐Attribute Procurement Mechanisms for Assortment Planning

Abstract: This research investigates how to design procurement mechanisms for assortment planning. We consider that a retailer buys directly from a manufacturer who possesses private information about the per-unit variable cost and per-variety setup cost. We first develop a screening model to assist the retailer in integrating assortment planning into supply chain contracting processes when only one manufacturer is available. We demonstrate that the screening mechanism is optimal among all feasible procurement strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Aydin and Hausman () find that slotting fees can induce the retailer to offer the supply‐chain‐optimal assortment. Li, Shao, and Sun () develop a multidimensional screening model in which manufacturers (i.e., potential suppliers to a retailer) have private information on costs and bid in a Vickrey auction for the opportunity to supply that retailer. Chu () concludes that screening with slotting allowances can yield higher total channel profits and higher social welfare.…”
Section: Resultsmentioning
confidence: 99%
“…Aydin and Hausman () find that slotting fees can induce the retailer to offer the supply‐chain‐optimal assortment. Li, Shao, and Sun () develop a multidimensional screening model in which manufacturers (i.e., potential suppliers to a retailer) have private information on costs and bid in a Vickrey auction for the opportunity to supply that retailer. Chu () concludes that screening with slotting allowances can yield higher total channel profits and higher social welfare.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers studied the supply chain contract design with asymmetric information as summarized in Table . First, most of the researchers considered asymmetric cost information in their supply chain contracting models (Corbett, Zhou, & Tang, ; Mukhopadhyay et al., ; Chaturvedi & Martínez‐de‐Albéniz, ; Özer and Raz, ; Çakanyıldırım, Feng, Gan, & Sethi, ; Fang, Ru, & Wang, ; Li, Shao, & Sun, ; Wagner, ). Comparatively, the supply chain contract design with asymmetric demand information has attracted less attention (Cachon, ; Chen, ; Kalkanci & Erhun, ; Lee & Yang, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, with respect to the characteristics of asymmetric information, there are more researchers considering the binary opposite asymmetric information for both suppliers and manufacturers (Cachon, ; Özer & Raz, ; Çakanyıldırım et al., ; Lee & Yang, ; Fang et al., ; Li et al., ; Wagner, ) than the continuous asymmetric information (Corbett et al., ; Chen, ; Mukhopadhyay et al., ; Chaturvedi Martínez‐de‐Albéniz, ; Kalkanci & Erhun, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The celebrated newsvendor model has well demonstrated that when the buyer faces uncertain demand, the optimal order quantity should depend on the purchasing price. To improve procurement efficacy, reverse auctions with order quantities dependent on bids receive increasing attention (e.g., Chen, 2007;Duenyas, Hu, & Beil, 2013;Li, Shao, & Sun, 2015). As a natural basis of supplier competition and a key determinant in the buyer's quantity decision, wholesale price bidding is a simple and commonly used instrument in procurement auctions (e.g., Li & Scheller-Wolf, 2011;Budde & Minner, 2014).…”
Section: Introductionmentioning
confidence: 99%